Drug Utilization Study in Ophthalmology Outpatient Department of a Tertiary Care Teaching Hospital - Mohammed, Sarfaraz; Thomas, Aksa Maria; Joy, Anju; Abraham, Annura Ann; Sravya, Devathi; Hiremath, Doddayya (Journal of Pharmacy Practice and Community Medicine)
Background: World Health Organization (WHO) has defined drug utilization in 1977 as marketing, distribution, prescription and use of drugs in a society with special emphasis on the resultant medical and social consequences. It should be evaluated periodically to increase the therapeutic efficacy and decrease adverse effects. Objectives: The aim of study is obtain data on the current prescribing pattern and drug utilisation trend of ophthalmologist in a tertiary care teaching hospital with ultimate goal to promote appropriate use of drugs. Methods: This prospective interventional study was conducted in 272 patients of either sex visiting Ophthalmology outpatient department over a period of six months at NMCH and RC, Raichur, Karnataka. The data collected from data collection form was analysed with the help of WHO prescribing indicators and evaluated using descriptive statistics. Results: Prescription analysis showed that the average number of drugs per prescription was 2.45. Drugs were mostly prescribed by brand name (98.5%), Eye drops (69%) were most prescribed dosage form, Injections (0.75%) were least prescribed, drugs prescribed from Essential Drug List was 50.9%. Antibiotics were most prescribed class of drugs (49.62%). Dosage form, frequency and duration of therapy were recorded in 100%, 95.5% and 84% of prescriptions. Conclusion: Polypharmacy was slightly seen in prescriptions. Antibiotics were highly used. The most commonly prescribed dosage form was eye drops. Half of drugs were prescribed from Essential drug list (EDL). Physicians preferred branded drugs rather than generic drugs. Diagnosis of the patient was not recorded for most of the prescriptions.
Keywords: Drug utilization evaluation; WHO core drug prescribing indicators; Polypharmacy; Generic name; Ophthalmology.